The Contingent Valuation Method contributes solutions for wildlife conservation: A case study at the Sepilok Orangutan Rehabilitation Centre in Borneo, Malaysia - Fazilah Musa; Damri Darman (Society of Environmental Toxicology and Chemistry, 2022)
Deforestation is an alarming issue that is prolific throughout world forests. Endemic fauna, flora, and wildlife habitat loss are serious concerns for world heritage. That is why Goal 15 of the Sustainable Development Goals (SDGs) promotes the conserved use of these natural resources. Sabah, Malaysia is fortunate to have “Orang Hutan” literally “Jungle People” in the Sepilok Forest area. The government had designated the Sepilok Orangutan Rehabilitation Centre as their safeguard. Indeed, this is the world's first Rehabilitation Centre for Orangutans. However, the wildlife conservation of Orangutans needs to be translated into economic values. This study aims to determine the economic valuation of wildlife conservation through visitors' Willingness to Pay (WTP) via applying the Contingent Valuation Method (CVM). A total of 143 questionnaires were distributed randomly to international and local visitors. The Logistic Regression was used to estimate the Mean WTP. Results showed that several significant sociodemographic variables influence the respondents' WTP. Nevertheless, most respondents were willing to pay a maximum of MYR16.73, while the mean was MYR7.27 only. In 2017, the estimated annual economic value of the Rehabilitation Centre was MYR9, 697 074.96 compared to the estimated conservation value of MYR96, 970 749.60. The findings of this study demonstrate the possible beneficial role of economic valuation in assisting not just Orangutan conservation but threatened species conservation elsewhere. The study has assisted the Centre's management in determining the appropriate entrance fees for the future, as they have not been revised in over a decade.